MATHEMATICAL LEARNING OUTCOME DIFFERENCES THROUGH THE IMPLEMENTATION OF COOPERATIVE LEARNING MODEL OF THINK PAIR SHARE TYPE, TWO STAY TWO STRAY TYPE, AND NUMBER HEAD TOGETHER TYPE - Fitriani Nur; Nur Khalisah Latuconsinah; Andi Ika Prasasti Abrar; Thamrin Tayeb; Ira Syamsuarni (MaPan : Jurnal Matematika dan Pembelajaran, 2018)
Abstract:The study aims to find out the students’ mathematical learning outcome differences through the implementation of cooperative learning model of Think Pair Share (TPS) type, Two Stay Two Stray (TSTS) type, and Numbered Heads Together (NHT) type. The study used quasi-experimental research design. The population of this study was all the second grade students of SMPN 1 Pallangga that consisted of 11 classes with the total number of 343 students. The sample was determined by using purposive sampling technique. The data analyses techniques used were descriptive and inferential statistics by using F one-way Anova test and follow-up testing by using Scheffe test. Based on the statistics analysis, it was found that there were the students’ mathematical learning outcome differences through the implementation of Think Pair Share (TPS) type, and Two Stay Two Stray (TSTS) type at the second grade of SMPN 1 Pallangga. Based on the mean scores, the highest score of the students’ learning outcomes was the experimental class implemented learning model of TPS type.Abstrak:Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar matematika siswa melalui penerapan model pembelajaran kooperatif tipe Think Pair Share (TPS), Two Stay Two Stray (TSTS), dan Numbered Heads Together (NHT). Jenis penelitian ini menggunakan quasi experiment. Populasi pada penelitian ini adalah seluruh peserta didik kelas VII SMPN 1 Pallangga yang terdiri dari 11 kelas, yang berjumlahkan 343 siswa. Penentuan sampel dengan menggunakan teknik purposive sampling. Teknik analisis data yang digunakan adalah statistik deskriptif dan analisis statistik inferensial dengan menggunakan uji F one-way Anava dan uji lanjut dengan menggunakan uji Scheffe. Berdasarkan analisis statistika menunjukkan bahwa terdapat perbedaan hasil belajar matemaika siswa melalui penerapan model pembelajaran kooperatif tipe Think Pair Share (TPS), Two Stay Two Stray (TSTS), dan Numbered Heads Together (NHT) pada kelas VII SMPN 1 Pallangga. Berdasarkan nilai rerata, hasil belajar matematika siswa yang tertinggi adalah kelas eksperimen yang menerapkan model pembelajaran tipe TPS.